Cerebellar Lobules Optimal Stimulation (CLOS): A Computational Pipeline to Optimize Cerebellar Lobule-Specific Electric Field Distribution - Rezaee, Zeynab; Dutta, Anirban (Frontiers in Neuroscience, 2019)
Objective: Cerebellar transcranial direct current stimulation (ctDCS) is challenging due to the complexity of the cerebellar structure which is reflected by the well-known variability in ctDCS effects. Therefore, our objective is to present a freely available computational pipeline to optimize lobule-specific electric field distribution using subject-specific head modeling. Methods: We present a novel approach that can optimize lobule-specific electric field distribution following finite element analysis (FEA) using freely available computational pipelines. The effects on lobule-specific electric field distribution of the subject-specific head model versus Colin 27 average head model was evaluated. Three published ctDCS montages, a 5cmx5cm anode was placed 3 cm lateral to inion, and the same sized cathode was placed on the contralateral supra-orbital area (called Manto montage) and buccinators muscle (called Celnik montage), and 4x1 HD-ctDCS electrode montage was implemented. Three-way Analysis of variance (ANOVA) was used to determine the effects of lobules, montage, and head model on the electric field distribution. Also, the uncertainty in lobule-specific electric field distribution for a subject-specific head model across different computational pipelines was evaluated using sensitivity analysis. Results: Eta-squared effect size after three-way ANOVA for electric field strength was 0.05 for lobule, 0.00 for montage, 0.04 for the head model, 0.01 for lobule*montage interaction, 0.01 for lobule* head model interaction, and 0.00 for montage*head model interaction in case of Enorm. Here, the electric field strength of both the Celnik and the Manto montages affected the lobules Crus II, VIIb, VIII, and IX of the targeted cerebellar hemispheres while Manto montage had a more bilateral effect. The 4X1 HD-ctDCS montage primarily affected the lobules Crus I, Crus II, VIIb of the targeted cerebellar hemisphere. Since all three ctDCS montages failed to target the cerebellar lobules related to ankle function so we presented an application of our computational pipeline to optimize a ctDCS electrode montage to deliver peak electric field at the cerebellar lobules VII-IX related to ankle function. Discussion: Our freely available computational modeling pipeline can be leveraged to optimize ctDCS electrode placement to target cerebellar lobules related to different cognitive and motor functions.